The Measurement of Language Lateralization with Functional Transcranial Doppler and Functional MRI: A Critical Evaluation - Somers, Metten; Neggers, Sebastiaan F.; Diederen, Kelly M.; Boks, Marco P.; Kahn, Rene S.; Sommer, Iris E. (Frontiers in Human Neuroscience, 2011)
Cerebral language lateralization can be assessed in several ways. In healthy subjects, functional MRI (fMRI) during performance of a language task has evolved to be the most frequently applied method. Functional Transcranial Doppler (fTCD) may provide a valid alternative, but has been used rarely. Both techniques have their own strengths and weaknesses and as a result may be applied in different fields of research. Until now, only one relatively small study (n=13) investigated the correlation between lateralization indices measured by fTCD and fMRI and showed a remarkably high correlation. To further evaluate the correlation between lateralization indices measured with fTCD and fMRI, we compared lateralization indices of twenty-two healthy subjects (twelve left- and ten right-handed) using the same word generation paradigm for the fTCD as for the fMRI experiment. Lateralization indices measured with fTCD were highly but imperfectly correlated with lateralization indices measured with fMRI (Spearman’s rho=0.75, p<0.001). The imperfectness of the correlation can partially be explained by methodological restrictions of fMRI as well as fTCD. Our results suggest that fTCD can be a valid alternative for fMRI to measure lateralization, particularly when costs or mobility are important factors in the study design.